Memahami Pesan Kampanye Politik Dalam Permainan Selamatkan Jakarta - Khosiah, Khosiah (Universitas Semarang, 2013)
Khosiah, G.331.09.0056. Understanding Political Campaign Message in Selamatkan Jakarta Game. Skripsi: Study Programme S-1 Communication Science Semarang University. The aim of the research to understand the message of political campaign in Selamatkan Jakarta Game. The theory base used in this research is the approach marks by Charles Sanders Peirce (in Littlejohn, 2009:64) defines semiosis as